The harmless imitator of OSCC: TUGSE - traumatic ulcerative granuloma with stromal eosinophilia - Pai, Anuradha; Yadav, Karthik D; T, Ramakrishna; B, Abhishek (Journal of Oral and Dental Sciences, 2017)
Traumatic Ulcerative Granuloma with Stromal Eosinophillia is a rare, benign, self-limiting and asymptomatic lesion that shows a spontaneous regression. Its etiopathogenesis is an enigma, but trauma seems to play a role for the occurrence of this lesion. Clinically it manifests as an isolated long standing lesion predominantly located in the tongue, demonstrating raised & indurated margins and mimicking oral squamous-cell carcinoma. Microscopically it is characterized by an inflammatory infiltrate rich in eosinophils. Since these lesions show delayed healing, treatment becomes necessary, but in certain cases, healing occurs by excision of the ulcer alone during the biopsy.
Keywords: Traumatic Ulcerative Granuloma with Stromal Eosinophilia; Oral Squamous-Cell Carcinoma; Mucoepidermoid Carcinoma; Adenoid Cystic Carcinoma; Self-Limiting